Donald R. Richberg papers - Richberg, Donald R. (Donald Randall), 1881-1960.
Correspondence, speeches, writings, interviews, subject files, printed matter, photographs, and other papers relating chiefly to Richberg's service during the New Deal era including his work as adviser to President Franklin D. Roosevelt in formulating the National Industrial Recovery Act of 1933, general counsel and chairman of the U.S. National Recovery Administration, and executive director of the National Emergency Council (U.S.). Includes material pertaining to Richberg's authorship of labor legislation and to his political career in the Bull Moose movement, as director of the National Legislative Reference Bureau of the Progressive Party, and later as a conservative. Also includes material on his law practice in Washington, D.C., and on his literary and public speaking career.
Correspondents include David Tennant Bryan, George Creel, Herbert David Croly, Allen B. Crow, Homer S. Cummings, Clarence Darrow, Joseph Edward Davies, Cecil B. DeMille, Felix Frankfurter, Albert W. Hawkes, Herbert Hoover, B.E. Hutchinson, Edward F. Hutton, Harold L. Ickes, Joseph P. Kennedy, James Jackson Kilpatrick, William Draper Lewis, David Eli Lilienthal, Ben B. Lindsey, Peter Locke, John S. Lord, Marvin Hunter McIntyre, Charles Edward Merriam, Ben Moreell, Frances Perkins, A. Willis Robertson, Eleanor Roosevelt, Theodore Roosevelt, Samuel I. Rosenman, Edward A. Rumely, Richard B. Russell, Amos Alonzo Stagg, Gerard Swope, DeWitt Wallace, and Edwin Watson.
Lawyer, author, and public official.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bryan, D. Tennant -- 1906-1998 -- Correspondence; Creel, George, -- 1876-1953 -- Correspondence; Croly, Herbert David, -- 1869-1930 -- Correspondence; Crow, Allen B. -- Correspondence; Cummings, Homer S. -- 1870-1956 -- Correspondence; Darrow, Clarence, -- 1857-1938 -- Correspondence; Davies, Joseph Edward -- Correspondence; DeMille, Cecil B. -- 1881-1959 -- Correspondence; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Hawkes, Albert W. -- 1878-1971 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; Hutchinson, B. E. -- 1888-1961 -- Correspondence; Hutton, Edward F. -- 1875-1962 -- Correspondence; Ickes, Harold L. -- 1874-1952 -- Correspondence; Kennedy, Joseph P. -- 1888-1969 -- Correspondence; Kilpatrick, James Jackson, -- 1920-2010 -- Correspondence; Lewis, William Draper, -- 1867-1949 -- Correspondence; Lilienthal, David Eli, -- 1899-1981 -- Correspondence; Lindsey, Ben B. -- 1869-1943 -- Correspondence; Locke, Peter, -- -1960 -- Correspondence; Lord, John S., -- 1881-1979 -- Correspondence; McIntyre, Marvin Hunter, -- 1878-1943 -- Correspondence; Merriam, Charles Edward, -- 1874-1953 -- Correspondence; Moreell, Ben, -- 1892-1978 -- Correspondence; Perkins, Frances, -- 1880-1965 -- Correspondence; Robertson, A. Willis -- 1887-1971 -- Correspondence; Roosevelt, Eleanor, -- 1884-1962 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Rosenman, Samuel I. -- 1896-1973 -- Correspondence; Rumely, Edward A. -- 1882-1964 -- Correspondence; Russell, Richard B. -- 1897-1971 -- Correspondence; Stagg, Amos Alonzo, -- 1862-1965 -- Correspondence; Swope, Gerard, -- 1872-1957 -- Correspondence; Wallace, DeWitt, -- 1889-1981 -- Correspondence; Watson, Edwin -- 1883-1945 -- Correspondence; United States; National Emergency Council (U.S.); Progressive Party (1912); American literature; Conservatism -- United States; Industrial policy -- United States; Labor laws and legislation -- United States; New Deal, 1933-1939.; Practice of law -- Washington (D.C.); Progressivism (United States politics); United States -- Economic conditions -- 1918-1945.; United States -- Economic policy -- 1933-1945.; United States -- Politics and government -- 1933-1945.; Authors; Lawyers; Public officials